Role of Higher Education Institution in Spatial Polarization of Youth - Gabdrakhmanov, Niyaz Kamilevich; Nikiforova, Nina Yurievna (Economy of Regions, 2019)
The expansion of applicants’ opportunities for choosing a university, unfortunately, did not completely eliminate the spatial factor in the process of selecting an educational institution. The majority of students are still graduates of local schools. The conducted analysis allows considering university as an element of the implementation of the strategic goal aimed at preserving and attracting human resources, as well as accumulating human capital. Thereby, it confirms that universities play an important role in the region’s socio-economic development by preserving and attracting youth of youth. For analysing the demographic consequences of the spatial polarization of youth we used the Lexis grid. The curve of the dynamics of the number of cohorts, built on the basis of the grid, revealed the most mobile group among the population aged from 17 to 19. The analysis of the existing Russian and foreign approaches to assessing the university’s role in regional development made possible making an analogy with the law of universal gravitation concerning this study. We proposed a gravity model and tested it at Kazan Federal University, one of ten federal Russian universities. The results of the study allowed assessing the spatial effect of the university on the polarization of youth. In this study, we hypothesised that there is a neighbourhood effect in higher education, namely an educational migration between neighbouring regions with different levels of socio-economic development. We tested this hypothesis in the geographical framework of the Volga Federal District using the official statistics and admission data of Kazan Federal University. The constructed gravity model of the university allowed assessing the scale and strength of this influence on attracting applicants from neighbouring subjects. Moreover, it allowed determining the regions of potential growth of influence. Such regions include the Republic of Chuvashia, the Orenburg Region and the Republic of Bashkortostan due to demographic conditions, logistics and the positioning of Kazan Federal University in the Volga Federal District.